2021
DOI: 10.1088/1748-9326/ac08c3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-data assessment of land use and land cover emissions from Brazil during 2000–2019

Abstract: Brazil is currently the largest contributor of land use and land cover change (LULCC) carbon dioxide net emissions worldwide, representing 17%–29% of the global total. There is, however, a lack of agreement among different methodologies on the magnitude and trends in LULCC emissions and their geographic distribution. Here we perform an evaluation of LULCC datasets for Brazil, including those used in the annual global carbon budget (GCB), and national Brazilian assessments over the period 2000–2018. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 41 publications
2
17
1
Order By: Relevance
“…For reconstructing land use, country-reported data on agricultural areas and forest harvest, often from FAOSTAT [85] and the Forest Resource Assessments [86], is typically included to isolate the anthropogenic signal [82]. Integrating better satellite-based and country-reported data on a global scale is clearly a promising path towards reducing the uncertainties around land use dynamics, but also the translation of country-reported data to land use dynamics as input to models could be substantially improved: Rosan et al [87] point out that retrospective updates in data reported by Brazil to FAO caused discrepancies between agricultural expansion and forest cover changes, which were attributed to the FAO "other land" category and thus remained unused by current global datasets [88], although they may contain part of a land use-induced deforestation signal. Additional uncertainties arise from the translation of land use data into land cover conversion [89].…”
Section: Spotlight: Why Are Uncertainties In Lulcc-related Ghg Fluxes...mentioning
confidence: 99%
“…For reconstructing land use, country-reported data on agricultural areas and forest harvest, often from FAOSTAT [85] and the Forest Resource Assessments [86], is typically included to isolate the anthropogenic signal [82]. Integrating better satellite-based and country-reported data on a global scale is clearly a promising path towards reducing the uncertainties around land use dynamics, but also the translation of country-reported data to land use dynamics as input to models could be substantially improved: Rosan et al [87] point out that retrospective updates in data reported by Brazil to FAO caused discrepancies between agricultural expansion and forest cover changes, which were attributed to the FAO "other land" category and thus remained unused by current global datasets [88], although they may contain part of a land use-induced deforestation signal. Additional uncertainties arise from the translation of land use data into land cover conversion [89].…”
Section: Spotlight: Why Are Uncertainties In Lulcc-related Ghg Fluxes...mentioning
confidence: 99%
“…Carbon fluxes are based on country‐level surveys of vegetation and soil carbon density for different forest ecosystems and response curves for temporal carbon dynamics following disturbance and recovery, for example, legacy fluxes and regrowth. More recently, satellite‐based biomass data are being used in book‐keeping approaches (e.g., Rosan et al., 2021) to more accurately reflect spatial variation in carbon stocks, and implicitly include the influence of environmental factors.…”
Section: The Terrestrial Carbon Cyclementioning
confidence: 99%
“…Carbon fluxes are based on country-level surveys of vegetation and soil carbon density for different forest ecosystems and response curves for temporal carbon dynamics following disturbance and recovery, for example, legacy fluxes and regrowth. More recently, satellite-based biomass data are being used in book-keeping approaches (e.g., Rosan et al, 2021) to more accurately reflect spatial variation in carbon stocks, and implicitly include the influence of environmental factors.…”
Section: Progress In Modeling Forest Land Use Changementioning
confidence: 99%